Cross-dehydrogenative coupling of α-C(sp3)–H of ethers/alkanes with C(sp2)–H of heteroarenes under metal-free conditions. Issue 46 (30th September 2015) - Ambala, Srinivas; Thatikonda, Thanusha; Sharma, Shweta; Munagala, Gurunadham; Yempalla, Kushalava Reddy; Vishwakarma, Ram A.; Singh, Parvinder Pal
Abstract : A metal-free cross-dehydrogenative coupling method between α-oxyalkyl/alkyl radicals and electron deficient heteroarenes is reported. Abstract : Here we have developed an effective metal-free dehydrogenative coupling method wherein α-oxyalkyl and alkyl radicals were generated from various ethers and alkanes to undergo coupling with a variety of electron-deficient heteroarenes such as un/substituted iso-quinolones, quinolines, pyridines, pyrazines and pyrimidines. The persulfate–acetone–water system was optimized for the dehydrogenative coupling with cyclic ethers which gave moderate to excellent yields of α-oxyalkyl containing heteroarenes. We have also optimized the conditions for coupling with cyclic alkanes and alicyclic ethers and demonstrated by conducting the reactions with a variety of electron-deficient heteroarenes. Further, the present method is also applicable to electron deficient arenes like naphthoquinones and moreover, it didn't require any external acid.